Penerapan Tekhnik Jigsaw Dalam Meningkatkan Hasil Belajar Bahasa Indonesia - Sofyan, Sofyan (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this research is to know the application of jigsaw technique can improve the learning result of Bahasa Indonesia on the material of inference of speech, lecture, sermon in class IX.3 SMP Negeri 1 Kisaran academic year 2017/2018. The subject of this research is the students of class IX.3 SMP Negeri 1 Kisaran academic year 2017/2018. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analysis result, it is found that the complete student has improved from the initial test until cycle II, that is the initial test (28,58%), cycle I (57,14%), cycle II (85,71%). The conclusion of this research is the application of jigsaw technique can improve the learning result of Indonesian students on the material of inference of speech, lecture, sermon in class IX3 SMP Negeri 1 Kisaran academic year 2017/2018. Keyword: jigsaw, speeche, lecture, sermon Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui penerapan tekhnik jigsaw dapat meningkatkan hasil belajar Bahasa Indonesia pada materi penyimpulan pidato, ceramah, khotbah di kelas IX.3 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018. Subjek penelitian ini adalah siswa kelas IX.3 SMP Negeri 1 Kisaran tahun pelajaran 2017/2018. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analisis didapatkan bahwa siswa yang tuntas mengalami peningkatan dari tes awal sampai siklus II, yaitu tes awal (28,58%), siklus I (57,14%), siklus II (85,71%). Kesimpulan dari penelitian ini adalah penerapan tekhnik jigsaw dapat meningkatkan hasil belajar Bahasa Indonesia siswa pada materi penyimpulan pidato, ceramah, khotbah di kelas IX3 SMP Negeri 1 Kisaran tahun pelajaran 2017/2018. Kata kunci: jigsaw, pidato, ceramah, khotbah